2020
DOI: 10.1186/s12879-020-4931-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of viral sexually transmitted infections and HPV high-risk genotypes in women in rural communities in the Department of La Paz, Bolivia

Abstract: Background: Bolivia has the highest prevalence of cervical cancer in South America and the prevalence of viral sexually transmitted infections (STIs) among people in urban cities is increasing. Little is known about the prevalence of viral STIs in rural communities, which generally have limited access to health care. In order to study the prevalence of viral STIs in rural Bolivia, we recruited women from villages and towns in the Department of La Paz in Bolivia. Methods: Three hundred ninety-four female partic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…In 2014, Tera ´n Caldero ´n [19] enrolled 868 women reporting a prevalence of 18.1% with HPV 16 as the most prevalent type (3.7%), followed by 31, 52 and 51. In 2020, Patzi-Churqui and co-workers [20] enrolled 364 women and reported a prevalence by genotype very similar to those of our study, even taking into account the different method used for testing: the most prevalent high-risk HPV types were HPV 56, 39 and 31, followed by HPV 16 and 18. The genotyping results of our survey are consistent with data reported in these studies.…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…In 2014, Tera ´n Caldero ´n [19] enrolled 868 women reporting a prevalence of 18.1% with HPV 16 as the most prevalent type (3.7%), followed by 31, 52 and 51. In 2020, Patzi-Churqui and co-workers [20] enrolled 364 women and reported a prevalence by genotype very similar to those of our study, even taking into account the different method used for testing: the most prevalent high-risk HPV types were HPV 56, 39 and 31, followed by HPV 16 and 18. The genotyping results of our survey are consistent with data reported in these studies.…”
Section: Plos Onesupporting
confidence: 82%
“…Cervical cancer represents the main cause of death of women in Bolivia [3]. However, compared to other Latin American countries, data on HPV prevalence are scarce and fragmented and often not representative of the great socio-environmental variability of the Bolivian territory [18][19][20]. Therefore, the Bolivian Ministry of Health promoted a national vaccination…”
Section: Discussionmentioning
confidence: 99%
“…This latter region could be considered as mostly rural, and it is known that rural communities are typically more conservative than urban communities. Different studies from diverse geographical areas/countries reported that HPV infection prevalence was higher in urban than rural areas [ 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In regions where HIV prevalence is high, there are also high prevalence rates of tuberculosis 179 , human papilloma virus (HPV) 180,181 , and herpes simplex virus 2 (HSV-2) 182 . The presence of inflammatory conditions in the genital tract, such as during a pre-existing HSV-2 183 or HPV infection, increases the risk of HIV-1 acquisition 181 .…”
Section: Hiv-1 Co-infectionmentioning
confidence: 99%